Association between Leukemia and Exon 2 CD19 Gene Variants in a sample of Iraqi Patients - Ahmed, Najwa Sh.; Al –Hadeithi, Zeina S. M.; Nada, Saad M.; Hadi, Yasameen Ali (Journal of the Faculty of Medicine Baghdad, 2015)
Background: The human CD19 (Cluster Differentiation) antigen is a 95 kd transmembrane glycoprotein belonging to the immunoglobulin superfamily. CD19 gene located on the short arm of chromosome 16p11.2 (P: petit). CD19 is a member of the Ig immunoglobulin superfamily expressed on the surface of B lymphocytes, and may play a pivotal role in B-cell differentiation and activation. Research suggests that mutations in a gene CD19 leads to a lack of expression of CD19 membrane and result in an antibody deficiency syndrome. Objective: The aim of this work is to study the mutations in Exon 2 CD19gene in leukemia patients in Baghdad/Iraq. Patients and Methods: This cross sectional study was performed in the National Center of Hematological Diseases/Al Mustanisyria University. Blood samples were collected from 50 leukemia patients including (25 acute lymphocyte leukemia ALL and 25 chronic lymphocyte leukemia CLL) and 50 samples of apparently healthy individuals. DNA was isolated and the CD19 gene was amplified by using specific primers for exon2 of this gene. The nucleotide sequences of CD19 gene was according to Macro gene company, USA. Analysis was done using BLAST program which is available online at (http:// www.ncbi.nlm.nih.gov) and BioEdit program. Results: The DNA sequencing results of flank sense of CD19 gene from healthy individual was found to be compatible 100% with wild type of Homo sapiens from the Gene Bank, while 99% compatibility was found for that gene of all ALL and CLL patients with wild type of gene. The difference was attributed to insertion of 1900 C nucleotide in position +48 of exon 2 of CD19 gene resulted in the replacement of a serine (TCC) residue into isoluseine (ATC), and deletion 1904 C in position + 49 of exon 2. This mutation resulted in change of codon from GCA to GCC but there was no changes in the amino acid (Alanine to Alanine). The second mutation (Deletion nucleotide) amended the first mutation effect (Insertion nucleotide) and did not lead to a change of all the amino acid sequence (framshift). The results showed that the incidence of insertion and deletion mutation at position +48 and +49 in exon 2 of CD19 gene and leukemia was highly significant (X2 = 15.75, P<0.01). Conclusion: This study suggests that the ploymrphism in exon 2 of the CD19 gene is strongly associated with leukemia patient of Baghdad population.